Does the Maternal Serum IgG Level during Pregnancy in Primary Antibody Deficiency Influence the IgG Level in the Newborn? - Vasantha Nagendran; Noel Emmanuel; Amolak S. Bansal (Case Reports in Immunology)
Purpose. To find out if the serum IgG level in the newborn baby was affected by low maternal serum IgG during pregnancy in two newly diagnosed primary antibody deficient patients. Method. Infant cord blood IgG level was compared with maternal IgG level in 2 mothers with newly diagnosed primary antibody deficiency, who declined replacement IgG treatment during pregnancy. Results. Both mothers delivered healthy babies with normal IgG levels at birth. Conclusions. The normal IgG levels and sound health in these 2 babies in spite of low maternal IgG throughout pregnancy raise interesting discussion points about maternofoetal immunoglobulin transport mechanisms in primary antibody deficiency.